TAFSIR FEMINISME ISLAM - Anam, Haikal Fadhil (MAGHZA, 2019)
Often, Q.S al-Nisa [4]: ??34 becomes a legitimacy that men are above the level of women especially in the words al-Rijalu Qawwamuna ala al-Nisa. Understanding men is a leader for women has implications for a subordination of women. Women are often regarded as second class in life. Most of the scholars also interpreted this way, that men are leaders for women. However, it is different from Riffat Hassan who was present with his reinterpretation contribution to the letter. Riffat Hassan, who is a feminist activist, criticized the interpretation of the ulemas. This article will describe the results of a study of Riffat Hassan's interpretation of Q.S al-Nisa [4]: ??34. This research is a literature study, with the authors using the method of library research. The data source of this research is the work of Riffat Hassan and books or other scientific works that are relevant to the focus of writing. Based on the results of the study, Riffat Hassan's interpretation of Q.S al-Nisa [4]: ??34 was much influenced by feminism. In his interpretation, he criticized previous scholars who interpreted the word qawwam as a leader. According to him if the word is interpreted as a leader, it will have implications for theology and psychology of the superiority of men over women. He offers the results of interpretation which is better if the word is interpreted as a protector and support. That way will have better implications if the view is that men are the support and protectors of women than men over women.